Development Strategy of Halal Food Industry to Enhance Consumption Activities in the Community of Medan City - Ahmad Kurnia; Marliyah; Juliana Nasution (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to discover how the primary priority strategies for the development of the Halal Food Industry can enhance consumption activities in the community of Medan City by presenting the internal and external factors that have been undertaken thus far. Additionally, the researcher highlights several urgent measures that need to be implemented to ensure a more focused development of the Halal Food Industry. The method employed is qualitative, using SWOT analysis and QSPM analysis. The questionnaire was completed by a total of five respondents, five of whom were SME practitioners in Medan City and five of whom were expert professionals. Based on the SWOT analysis results, the strategy quadrant derived after processing through the IFE and EFE matrices falls within Quadrant I. This indicates that the strategy employed is a progressive one. This strategy signifies that the Halal Food industry possesses strengths and opportunities. Moving forward to the QSPM analysis, the outcome indicates that the primary priority strategy to be undertaken is to capitalize on the Halal Product Training Program, thereby enabling the Halal Industry to tap into global markets.